Obesity and micronutrients deficit, when and how to suplement - Sebastián Pablo Chapela; Andres Luciano Nicolas Martinuzzi; Natalia Daniela Llobera; Florencia Ceriani; Victoria Gonzalez; Martha Montalvan; Ludovica Verde; Evelyn Frias-Toral (Food and Agricultural Immunology)
Since the 1990s the worldwide rate of obesity has escalated significantly. This overflow affects all demographic groups, with a notable impact on older adults and women. Obesity is associated with a variety of serious chronic health conditions. Additionally, it is linked to endocrine disorders such as hypothyroidism and subclinical hypothyroidism. This review analyzes the connection between obesity and micronutrient levels, particularly focusing on vitamin D, and evaluates potential nutritional and supplementation approaches for this population.Micronutrient imbalances in obesity arise from poor dietary intake, increased nutritional needs, altered pharmacokinetics, and absorption difficulties. These imbalances can lead to critical health and metabolic issues. For example, vitamin D deficiency, which is common in individuals with obesity, is associated with decreased calcium absorption and an incremented risk of type 2 diabetes, metabolic syndrome, and various inflammatory conditions such as cancer.Effectively addressing micronutrient deficiencies requires dietary modifications and, when necessary, supplementation. While enhancing nutrition is critical, supplementation often becomes essential to meet the nutritional needs of individuals with obesity, particularly those on restrictive diets or undergoing bariatric surgery. Supplementing micronutrients and vitamin D in patients with obesity can improve health related outcomes. Moreover, dietary patterns like the Mediterranean diet can increase vitamin D levels. This review underlines the crucial role of tailored supplementation strategies and the demand for continued research to ascertain optimal dosing and its implications for health outcomes.